2013
DOI: 10.1088/0957-0233/24/6/065803
|View full text |Cite
|
Sign up to set email alerts
|

Validation of low-cost ozone measurement instruments suitable for use in an air-quality monitoring network

Abstract: This paper presents a novel low-cost instrument that uses a sensor based on conductivity changes of heated tungstic oxide, which is capable of accurately measuring ambient concentrations of ozone. A combination of temperature steps and air flow-rate steps is used to continually reset and re-zero the sensor. A two-stage calibration procedure is presented, in which a nonlinear transformation converts sensor resistance to a signal linear in ozone concentration, then a linear correlation is used to align the calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(116 citation statements)
references
References 61 publications
3
113
0
Order By: Relevance
“…We compare the performance of our RF models to these studies in Table 3. While several low-cost sensor calibration studies have investigated calibration models within laboratory environments (Masson et al, 2015a;Mead et al, 2013;Piedrahita et al, 2014;Williams et al, 2013), we have elected to limit our comparison to field data.…”
Section: Comparison Of Results To Other Published Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We compare the performance of our RF models to these studies in Table 3. While several low-cost sensor calibration studies have investigated calibration models within laboratory environments (Masson et al, 2015a;Mead et al, 2013;Piedrahita et al, 2014;Williams et al, 2013), we have elected to limit our comparison to field data.…”
Section: Comparison Of Results To Other Published Studiesmentioning
confidence: 99%
“…Additionally, NO has also been observed to interfere with NO 2 , and CO sensors have exhibited some cross-sensitivity to molecular hydrogen in urban environments (Mead et al, 2013). Furthermore, low-cost sensors can be affected by meteorology (Masson et al, 2015b;Moltchanov et al, 2015;Pang et al, 2017;Williams et al, 2013). Most electrochemical sensors are configured such that the reactions are diffusion-limited, and the diffusion coefficient can be affected by temperature (Hitchman et al, 1997); Masson et al (2015b) have shown that at relative humidity (RH) exceeding 75 % there is significant error, possibly due to condensation on potentiostat electronics.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Williams and coworkers quantified a tungstic oxide ozone sensor in the lab while addressing some of the main drawbacks associated with Metal oxide (MOx) ozone sensors 20 (i.e. drift/long term stability, material degradation and sensitivity fluctuations) (Williams et al, 2013). Researchers also deployed these gas semiconductor sensors in British Columbia over roughly 10,000 km 2 for three months finding low errors (3 +/-2 ppb) between hourly averaged sensor and reference instruments while documenting the challenges of using, in this instance, wireless sensor networks (Bart et al, 2014).…”
mentioning
confidence: 99%
“…There are a number of empirical functions that can be used to calibrate the sensor. In [5], we illustrated a function derived from a theoretical model of the sensor response, (P):…”
Section: Drift Characteristicsmentioning
confidence: 99%
“…A critical issue is confirming the integrity and calibration of the sensor over time. Common issues in sensors can be effects of ambient conditions (e.g., sublimation of sensor material from high humidity [4], increasing baseline measurements [5], drifting calibration, and site impacts (e.g., dirt in inlets or power variations). Identifying changes in baseline or calibration so that action can be taken would improve management of such networks.…”
Section: Introductionmentioning
confidence: 99%